Pengalaman Sense of Smell pada Arsitektur Rumah Adat Suku Osing - Yusuf Ariyanto; Helen Saphira; Jason Santoso; Gwyneth; Albert Jonathan Tandiary (ATRIUM: Jurnal Arsitektur, 2024)
Title: Sense of Smell Experience on Osing Traditional House Architecture Nusantara architecture results from identical thinking on cultural background and natural conditions that produce physical comfort and atmosphere resulting from the response of human senses, one of which is the sense of smell. The study focuses on the influences or sense of smell responses associated with buildings, such as building materials used, softscape, and hardscape that produce certain scents, especially in Osing Tribe's Indigenous Houses. In line with that, the study identified smells through sensory mapping and the smell intensity influencing the atmosphere by superimposing a Likert scale with a smells wheel from two objects studied, Homestay Bata Merah and Villa SoLong in Banyuwangi. The results of this study found that building elements such as wood, terraces, natural stones, ceramics, paving blocks, and linen are the primary materials that give characteristic aroma, followed by vegetation such as trees that have flowers or sweet-aromatic fruit also dominate, especially in the Homestay Bata Merah. On the other hand, the typical smells are also formed by the influence of geographical conditions and wind movements as the medium of smells material spread, as in Vila SoLong, which has typical ocean smells. The sense of smell experience of traditional house buildings also shapes Nusantara Architecture's identity and improves the comfort of visitors or people active in it.